2013
DOI: 10.1111/ajt.12110
|View full text |Cite
|
Sign up to set email alerts
|

BK Polyomavirus in Solid Organ Transplantation

Abstract: The human BK polyomavirus (BKV) is the major cause of polyomavirus-associated nephropathy (Py-VAN) putting 1-15% of kidney transplant patients at risk of premature allograft failure, but is less common in other solid organ transplants. Because effective antiviral therapies are lacking, screening kidney transplant patients for BKV replication in urine and blood has become the key recommendation to guide the reduction of immunosuppression in patients with BKV viremia. This intervention allows for expanding BKV-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
518
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(543 citation statements)
references
References 108 publications
(150 reference statements)
21
518
2
2
Order By: Relevance
“…Disease Community of Practice guideline (38). The added value of our study lies particularly in the integrated evaluation of this serological marker among donor-recipient pairs because this provides leads for future algorithms to predict BKPyV-related disease after transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Disease Community of Practice guideline (38). The added value of our study lies particularly in the integrated evaluation of this serological marker among donor-recipient pairs because this provides leads for future algorithms to predict BKPyV-related disease after transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Polyoma virus nephropathy (PVN), which had not been recognized in 1991, renders TCMR lesions of uncertain significance (15), and the 1991 criteria must now be interpreted in biopsies with more aging, injury and scarring. This ''data drift''-a shift in disease prevalence and prior probabilities within the target population-is a common occurrence in epidemiological studies, and is to be expected in a diagnostic system in use for over two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Negative urine NAT for BKPyV has almost 100% NPV but patients with BKPyV viruria exceeding established thresholds should be tested additionally by NAT on the blood. 1,2 NAT in urine, in the absence of an elevated BKPyV plasma load is not associated with an increased risk for BKPyVAN. Pinto et al 7 concluded that positive BKPyV in two or more urine samples was helpful to predict BKPyV viremia with 100% sensitivity, 94% specificity and a PPV of 50% and NPV of 100%.…”
Section: Analysis Of Diagnostic Methods As a Screening Test To Detectmentioning
confidence: 83%
“…1,6 Currently, available screening tests include: urine cytology to identify virally loaded epithelial cells (also named "decoy cells"), quantitative nucleic acid amplification testing (NAT) by polymerase chain reaction (PCR) to identify BKPyV in urine or plasma or blood samples, or urine electronic microscopy to detect three-dimensional viral aggregates (Haufen). that directly compared the analytical performance of screening methods to predict the diagnosis of BKPyVAN proven by histopathology.…”
Section: Analysis Of Diagnostic Methods As a Screening Test To Detectmentioning
confidence: 99%
See 1 more Smart Citation